If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(1-7n)+5(1+7n)=2
We move all terms to the left:
-3(1-7n)+5(1+7n)-(2)=0
We add all the numbers together, and all the variables
-3(-7n+1)+5(7n+1)-2=0
We multiply parentheses
21n+35n-3+5-2=0
We add all the numbers together, and all the variables
56n=0
n=0/56
n=0
| 3/5c=-15 | | H(x)=4.9^2+50 | | 8x+2(x+6)=82 | | 5(c+3)=40 | | 5+3(1-5p)=-82 | | 10x-(9)x-2=24 | | 4(2-5b)=-112 | | (x+92)+(3x+60)=180 | | 3x÷(5)=7 | | 5(1+3x)=17+3x | | 190+350x=11+475x | | 6.3−5x=1.1-(3x+5.3) | | (5x-51)+(x+57)=180 | | 3x-(5)=7 | | 2x+3=7(2) | | (x-9)^7=1 | | 190+550x=110+675x | | 5/10=y/12 | | (11x-68)=97 | | 4x2+45x-350=0 | | 2x+3=7×2 | | 0.3/0.9=0.2/x | | 4x2−24x+7=3 | | 3-4y=27 | | 8x=298 | | 250x+200=375x+90 | | 8n=-40n | | 8+4a=5a | | 6(w-8)=4w-28 | | 1.50x+19=2.75x+8 | | 9x+8=10x+8x+10=180 | | 99-10x=11 |